2020
DOI: 10.1371/journal.pone.0233729
|View full text |Cite
|
Sign up to set email alerts
|

Plant life at the dry limit—Spatial patterns of floristic diversity and composition around the hyperarid core of the Atacama Desert

Abstract: Extreme arid conditions in the Atacama Desert in northern Chile have created a unique vegetation almost entirely restricted to the desert margins along the coast of the Pacific Ocean and the Andean range. In this study we provide data on the desert vegetation along elevational gradients at four localities from the western Andean slopes, between 19˚and 21˚S. Additionally, zonation of floristic data was explored. Three altitudinal zones could be classified and described in detail for each locality. Conspicuously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 39 publications
8
20
0
1
Order By: Relevance
“…The onset of hyperarid conditions during the early Pleistocene would have led to habitat fragmentation, promoted speciation, and possibly caused the disjunction of the Peruvian E. ritteri from the Chilean congeners. Despite a reported floristic break along the coast between northern Chile and southern Peru (Ruhm et al, 2020), several studies have reported a similar pattern of disjunct species distribution in other plant groups, such as Malesherbia , Nolana , and Cristaria (Gengler‐Nowak, 2002; Dillon et al, 2009; Böhnert et al, 2019). Although we favor here the contraction–expansion model of populations during climatic oscillations as the ultimate driver for speciation, we do not dismiss the importance of newly emerging pollination syndromes or local adaptation to edaphic factors as other important reasons for Eulychnia diversification.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of hyperarid conditions during the early Pleistocene would have led to habitat fragmentation, promoted speciation, and possibly caused the disjunction of the Peruvian E. ritteri from the Chilean congeners. Despite a reported floristic break along the coast between northern Chile and southern Peru (Ruhm et al, 2020), several studies have reported a similar pattern of disjunct species distribution in other plant groups, such as Malesherbia , Nolana , and Cristaria (Gengler‐Nowak, 2002; Dillon et al, 2009; Böhnert et al, 2019). Although we favor here the contraction–expansion model of populations during climatic oscillations as the ultimate driver for speciation, we do not dismiss the importance of newly emerging pollination syndromes or local adaptation to edaphic factors as other important reasons for Eulychnia diversification.…”
Section: Discussionmentioning
confidence: 99%
“…Life forms of species depend mainly on adaptation to the environment, particularly climate [ 66 , 67 , 68 , 69 ]. Life forms of desert plants are closely related to precipitation [ 70 , 71 ] and are correlated with both landform and topography [ 72 , 73 , 74 ]. In the present study, the chamaephyte life form was most represented (40%).…”
Section: Discussionmentioning
confidence: 99%
“…It encompasses a wide variety of environments, biotic communities, and species from the southern temperate forests (47 • lat S), to the margin of the Atacama Desert along the coast of Antofagasta to the Mejillones Peninsula, at a latitude close to the Tropic of Capricorn (23 • lat S) (Figure 1). The northern limit of this biodiversity hotspot is the margin of the Antofagasta coastal desert [15,16], which is also part of the Lomas Formation, an area extending from southern Peru to the north of La Serena city, Chile (El Tofo, 29.5 • lat S) [17][18][19] (Figure 1). The Lomas Formation spans tropical and subtropical latitudes and extends into the most arid part of the Atacama Desert as a result of the stable position of the Pacific Anticyclone [19].…”
Section: Introductionmentioning
confidence: 99%
“…The northern limit of this biodiversity hotspot is the margin of the Antofagasta coastal desert [15,16], which is also part of the Lomas Formation, an area extending from southern Peru to the north of La Serena city, Chile (El Tofo, 29.5 • lat S) [17][18][19] (Figure 1). The Lomas Formation spans tropical and subtropical latitudes and extends into the most arid part of the Atacama Desert as a result of the stable position of the Pacific Anticyclone [19]. The formation has a conspicuous vegetation that is expressed in the so-called 'fog oases', which are dependent on the continuous presence of sea fogs, or camanchacas (Figure 1).…”
Section: Introductionmentioning
confidence: 99%